Biological reactions of forests to climate change and air pollution - Matyssek, Rainer; Kozovits, Alessandra R.; Wieser, Gerhard; Augustaitiene, Ingrida; Augustaitis, Algirdas (European journal of forest research, 2014)
Issue Title: Special Section : Biological reactions of forests to climate change and air pollution